1965
DOI: 10.1128/jb.89.5.1340-1347.1965
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of Germination of Bacillus Spores

Abstract: The kinetics of germination of Bacillus cereus strain T spores was accurately described by McCormick. To study the mechanism of germination, it is necessary to correlate the characteristic changes in a population of germinating spores with the behavior of the individual spores in the same population. Two microscopic events are apparent during germination: microlag, the time interval between the addition of L-alanine to heat-activated spores and the beginning of loss in refractility, and microgermination time, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
0

Year Published

1985
1985
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(74 citation statements)
references
References 10 publications
11
63
0
Order By: Relevance
“…Determination of the reduction in spore optical density has also been used to assess spore germination. The percent germination can be calculated from the absorbance decrease at 625 nm, a 60% decrease of initial absorbance for intact spores represents 100% germination of the spore population (Vary 1965;Parker 1969;Boschwitz et al 1983;Power et al 1989;Senesi et al 1992;Makino et al 1994). Other methods used to study spore germination include determining the loss of heat resistance during germination (Warth 1978b), or the amount of dipicolinic acid (DPA) released by germinating spores (Janssen et al 1958;Warth 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Determination of the reduction in spore optical density has also been used to assess spore germination. The percent germination can be calculated from the absorbance decrease at 625 nm, a 60% decrease of initial absorbance for intact spores represents 100% germination of the spore population (Vary 1965;Parker 1969;Boschwitz et al 1983;Power et al 1989;Senesi et al 1992;Makino et al 1994). Other methods used to study spore germination include determining the loss of heat resistance during germination (Warth 1978b), or the amount of dipicolinic acid (DPA) released by germinating spores (Janssen et al 1958;Warth 1980).…”
Section: Introductionmentioning
confidence: 99%
“…Many investigators have analyzed the effects of heat treatment on the germination response of the spores of various species and strains (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). Effects of heat (i) on the dormant state prior to germination, (ii) on the trigger reaction of germination, and (iii) on the later events during germination are discussed below.…”
mentioning
confidence: 99%
“…Heat also changes reversibly the tertiary structure of a protein responsible for the maintenance of the dormant state of the B. cereu s spore, resulting in a change in the permeability (8). Activation often reduces the microlag of germination as shown in B. cereus spores (3,17). The second point is concerned with the modification by heat of the site(s) for the germinant or related compounds.…”
mentioning
confidence: 99%
“…One to two hours were needed for the majority of TrigoCor spores to germinate (Figs 1, 2, 4 and 5), which is longer than typical times reported for heat-activated Bacillus spores (Vary and Halvorson 1965;Hashimoto et al 1969;Atluri et al 2006), and similar or shorter than times commonly reported for non-heat-activated spores (Evans and Curran 1943;Kong et al 2011). The time required for Bacillus spore germination is dependent on the lag time between addition of germinant and release of DPA.…”
Section: Discussionmentioning
confidence: 63%
“…The time required for Bacillus spore germination is dependent on the lag time between addition of germinant and release of DPA. This lag time is variable between species, strains and even individual spores (Chen et al 2006;Zhang et al 2010;Setlow 2013) and is influenced by factors such as activation via heat treatment, concentration of germinant, type of germinant, temperature, number of germinant receptors present in spore membranes and storage conditions (Keynan et al 1964;Vary and Halvorson 1965;Zhang et al 2010Zhang et al , 2013Setlow 2013). Whereas the absence of a heat treatment likely lengthened the lag time of TrigoCor spores, it is possible that the lag time was also somewhat shortened due to the use of high germinant concentrations and/or germinants such as A-GFK which act on multiple germinant receptors.…”
Section: Discussionmentioning
confidence: 99%